2010
DOI: 10.1089/lap.2010.0007
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Analysis of the Learning Curve for Laparoscopic Rectal Cancer Surgery

Abstract: Multidimensional analysis considering various surgical outcomes is necessary to evaluate the learning curve for laparoscopic rectal cancer surgery. The effective surgical learning curve was approximately 60-80 procedures in this series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 31 publications
3
51
1
2
Order By: Relevance
“…According to author's current knowledge, there are no published reports about intra-operative doublestapled anastomotic complication from surgeons' experience. However, the result of this study is concordant with previous published reports that laparoscopic colorectal surgery can be performed safely during learning period [19][20][21].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…According to author's current knowledge, there are no published reports about intra-operative doublestapled anastomotic complication from surgeons' experience. However, the result of this study is concordant with previous published reports that laparoscopic colorectal surgery can be performed safely during learning period [19][20][21].…”
Section: Discussionsupporting
confidence: 92%
“…When 10.9 ± 6.2 11.5 ± 5.7 NS [19][20][21]. According to literature for the learning curve, we defined initial experience as first 70 laparoscopic colorectal resections.…”
Section: Discussionmentioning
confidence: 99%
“…23 Previous reports focused only on the total case numbers to reach the learning curve. 20,22,24 However, the consideration of operative frequency and reaching time can suggest a new aspect regarding the surgical training. In our study, surgery was performed on 1 to a maximum of 8 cases in a month by a single surgeon, and the learning curve period was reached in the 15th month by this frequency of laparoscopic right colectomy (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic surgeons, once having gained proficiency, become more prone to approach complex cases, leading to an apparent increase in the morbidity. 35,36 Only one study in the literature addressed the oncologic outcome as a parameter for evaluation of the learning curve. Smeenk and colleagues 11 divided the study group, comprising patients with PMP and peritoneal carcinomatosis from colorectal cancer, into 3 sequential subgroups, and observed that there were no significant differences among them in terms of prognosis.…”
Section: Discussionmentioning
confidence: 99%